Dataset on the crystallographic, vibrational, and electronic properties of 1M-phlogopite K(Mg,Fe)3(Si3Al)O10(OH)2 obtained from Density Functional Theory investigations - Gianfranco Ulian; Giovanni Valdrè (Data in Brief, 2023)
The present work reports a dataset on the crystal structure, optical properties (complex dielectric function and refractive index), infrared, reflectance and Raman spectra, and electronic properties (band structure and density of states) of the 1M-polytype of phlogopite [1]. This phyllosilicate presents chemical formula K(Mg,Fe)3(Si3Al)O10(OH)2, with Mg/Fe ratio ≥ 2. The dataset was obtained from Density Functional Theory (DFT) simulations at B3LYP-D* level, i.e., with the hybrid functional B3LYP corrected with an ad hoc DFT-D2 scheme, and all-electron Gaussian-type orbitals basis sets for all atoms in the unit cell. Furthermore, experimental confocal Raman micro-spectrometry data (spectra) collected on a single crystal phlogopite specimen are reported. The quality of the dataset was assessed by comparing the results with available X-ray diffraction and IR/Raman spectroscopy data reported in literature. The reported complete dataset is a reference for future studies in fundamental georesource exploration and exploitation, applied mineralogy, geology, and material science.